Kinetic study of esterification of fatty acids over calcium ferrite catalyst - Nurul Fatihah, Mahamad Roli (2014)
Biodiesel is a promising renewable alternative fuel to fossil energy. For the biodiesel production from non-edible oil feedstocks like Jatropha curcas oil, a pre-treatment step is essential, which is the esterification of free fatty acids in the feedstocks in order to avoid soap formation and minimize catalyst deactivation. The FFA used in this experiment was obtained by two methods which saponification, where oil (Jatropha oil) is converting to soap and also acidification, where the sodium salts of free fatty acids are converted to FFA by using hydrochloric acid (HCL). In this research, Calcium Ferrite (CaFe2O4) catalyst was prepared for the esterification of FFA. Due to its ability as an effective catalyst and without changing its crystal structure, Calcium Ferrite can yield high conversion of FFA into biodiesel. Calcium Ferrite catalyst was synthesized by Pechini method. Pechini process was newly used in this field of catalyst production. It is a powder-synthesis process that involves the formation of a polymeric precursors (resin), using citric acid and ethylene glycol. The molar ratio for citric acid monohydrate to ethylene glycol used in this experiment was 60:40. The calcinations behavior of the precursor powders of Calcium Ferrite was studied in the temperature range of 450-12000C in an air atmosphere. Characterization of the powder samples were performed using several processes including X-ray diffractometry (XRD), thermogravimetry (TGA) and Brunauer Emmett Teller (BET) analyzer. The effects of reaction temperature, methanol/FFA molar ratio, catalyst concentration on the FFA conversion were also studied. Based on the findings of this study, ethanol to FFA ratio of 30:1, 10 % weight of the catalyst, reaction time of 6 h and temperature 70 0C were found as the optimum for the esterification reaction. Therefore, the developed catalyst could be effectively used for the esterification of FFA in plant oil